Systematic Literature Review: Measurement Model of Lecturer Performance and Organizational Citizenship Behaviours Based on Work Environment Characteristics, Innovation and Knowledge Sharing - Nurhasanah, Nina; K, Purwanto S. (CENTRAL ASIA AND THE CAUCASUS, 2022)
Lecturer performance remains the main issue on improving the success of tridharma implementation on universities, influence on work environment, use of modern technology and sharing knowledge become an important matter to discuss, where the behavior of lecturers in doing their job is not only lecture but also include developing teaching materials, writing journals, guide their students and even activities outside their work hours. This is called Organizational Citizenship Behaviors. However, the lack of literature journals on these variables made researchers reluctant to research using these variables. The systematic literature review study on human resource management as a result from library research concluded that: 1) Work Environment affects Organizational Citizenship Behavior; 2) Innovation affects Organizational Citizenship Behavior; 3) Knowledge Sharing affects Organizational Citizenship Behavior; 4) Work Environment, Innovation and Knowledge Sharing simultaneously affect Organizational Citizenship Behavior; 5) Work Environment affects Lecturer Performance; 6) Innovation affects Lecturer Performance; 7) Knowledge Sharing affects Lecturer Performance; 8) Organizational Citizenship Behavior affect Lecturer Performance; 9) Work Environment, Innovation, Knowledge Sharing and Organizational Citizenship Behavior simultaneously affect Lecturer Performance.